Redescription of adults, nymphs and taxonomic notes on the Southern Brazilian mayfly Ulmeritus saopaulensis (Traver, 1946) (Ephemeroptera: Leptophlebiidae) - Silva,Vinícius de Assis (2022)
ABSTRACT The small mayfly genus UlmeritusTraver, 1956 currently includes three species of Neotropical Leptophlebiidae (Ephemeroptera) distributed in southern South America in the Pampean and Atlantic Forest dominions: U. carbonelli (Uruguay), U. balteatus (Brazil and Uruguay) and U. saopaulensis (Brazil). Ulmeritus saopaulensis is a poorly known endemic species from Brazil. Based on material from a single locality in Minas Gerais, we complement the knowledge on this species with a redescription of adults and nymphs and describe the eggs for the first time. The confusing nomenclatural history and the correct spelling of the specific name saopaulensis is discussed in light of International Code of Zoological Nomenclature. This paper points out that in despite of recent advances on the knowledge of this genus a full taxonomic review and phylogenetic analyses are pending to solve species delimitation and evolutionary relationships.